Pregnancy-induced brain magnetic resonance imaging changes in women with multiple sclerosis - Uher, Tomas; Kubala Havrdova, Eva; Vodehnalova, Karolina; Krasensky, Jan; Capek, Vaclav; Vaneckova, Manuela; Horakova, Dana (European journal of neurology, 2022)
BACKGROUND AND PURPOSE: The effect of pregnancy on brain changes and radiological disease activity in women with multiple sclerosis (MS) is not well understood. This study was undertaken to describe the dynamics of lesion activity and brain volume changes during the pregnancy and postpartum periods. METHODS: This observational study of 62 women with relapsing-remitting MS included magnetic resonance imaging (221 scans) as well as clinical visits at baseline (<24 and >6 months before pregnancy), prepregnancy (<6 months before pregnancy), postpartum (<3 months after delivery), and follow-up (>12 and <24 months after delivery) periods. RESULTS: The majority of women had a mild disability and a short disease duration (median = 5.5 years). Eighteen (29.0%) women had a relapse during the year preceding pregnancy onset, nine (14.5%) during pregnancy, and 20 (32.3%) in the year following delivery. Disability status remained unchanged during follow-up. Women in the postpartum period (n = 62) had higher T2 lesion volume (median = 1.18 ml vs. 0.94 ml), greater annualized T2 lesion volume increase (0.23 ml vs. 0.0 ml), lower brain parenchymal fraction (85.6% vs. 86.4%), and greater annualized brain volume loss (-1.74% vs. -0.16%) compared with the prepregnancy period (all p < 0.001). At 12-24 months after delivery, women (n = 41) had higher T2 lesion volume (1.16 ml vs. 1.0 ml) and lower brain parenchymal fraction (86.0% vs. 86.5%) compared to the prepregnancy period (both p < 0.001). CONCLUSIONS: The postpartum period was associated with an increase in T2 lesion volume and accelerated brain volume loss in a considerable proportion of women. This should be considered in treatment decision-making and designing clinical trials.
Keywords: relabující-remitující roztroušená skleróza; Magnetic Resonance Imaging; atrofie; mozek; lidé; Female; Multiple Sclerosis; Pregnancy; magnetická rezonanční tomografie; těhotenství; Atrophy; Brain; roztroušená skleróza; Multiple Sclerosis, Relapsing-Remitting; ženské pohlaví; Humans